(untitled) (LEARNing Landscapes, 2018)
In this interview, author, researcher, and professor D. Jean Clandinin reflects on her many years of experience as a narrative inquiry researcher, teacher, and teacher educator. She believes that growing up in a large, extended family with rooted engagement in the community set the stage for her later interest in narrative inquiry. She describes the many varied scholars who have had an influence on her and explains the basic tenets of narrative inquiry in both the classroom and research contexts. The challenges that face narrative inquiry researchers are described and she shares her vision of how things are changing. Finally, she tells one of her favorite narrative inquiry stories.